Area‐preserving curvature flow of one‐dimensional graphs and application to smoothing of dynamic PET data. Issue 14 (6th May 2015) - Baker, Charles
Abstract : We design two area‐preserving curvature flows of one‐dimensional graphs and analyse the asymptotic shape of the solutions. An application to the smoothing of curves generated in dynamic positron emission tomography (PET) is also presented.